Early palliative care - health services research and implementation of sustainable changes: the study protocol of the EVI project - Meffert, Cornelia; Bardenheuer, Hubert J.; Buchheidt, Dieter (BMC cancer, 2015)
International medical organizations such as the American Society of Medical Oncology recommend early palliative care as the “gold standard” for palliative care in patients with advanced cancer. Nevertheless, even in Comprehensive Cancer Centers, early palliative care is not yet routine practice. The main goal of the EVI project is to evaluate whether early palliative care can be implemented—in the sense of “putting evidence into practice”—into the everyday clinical practice of Comprehensive Cancer Centers. In addition, we are interested in (1) describing the type of support that patients would like from palliative care, (2) gaining information about the effect of palliative care on patients’ quality of life, and (3) understanding the economic burden of palliative care on patients and their families.